Binge drinking, crime and victimisation during bashes at the University of Limpopo - Matlou Malekgale, Lebogang (My University, 2017)
Binge drinking, crime and victimisation are increasingly being recognised as problems on university and college campuses. Binge drinking is a pattern of drinking that can lead to anti-social behaviour among students. This can lead to a number of negative individual and social effects such as crime and victimisation. The key concepts, binge drinking, crime and victimisation during bashes are defined in relation to the Lifestyle Exposure Theory and Routine Activities Theory. This is done within the concepts of the theories and in particular motivated offenders, suitable targets, in the absence of a capable guardian. The aim of the study was to describe binge drinking and its resultant criminological outcomes during bashes at the University of Limpopo. A qualitative design was used in this study. The sampling method that was used to select the participants was nonprobability sampling and specifically snowball sampling. Data was collected until the saturation point, where no new information occurred. To analyse the data, thematic content analysis was used.
Thesis (M.A. (Criminology)) -- University of Limpopo, 2017
Keywords: Binge drinking; Crime and victimisation; Bashes; University of Limpopo; Binge drinking; Alcohol; Students -- Crimes against -- South Africa -- Limpopo; Crime -- South Africa -- Limpopo; Victims of crimes surveys